2016
DOI: 10.1021/acs.langmuir.6b01925
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Protein Loading on Hierarchically Porous Layered Double Hydroxide Composites with a Rational Mesostructure

Abstract: Hierarchically porous biocompatible Mg-Al-Cl-type layered double hydroxide (LDH) composites containing aluminum hydroxide (Alhy) have been prepared using a phase-separation process. The sol-gel synthesis allows for the hierarchical pores of the LDH-Alhy composites to be tuned, leading to a high specific solid surface area per unit volume available for high-molecular-weight protein adsorptions. A linear relationship between the effective surface area, SEFF, and loading capacity of a model protein, bovine serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…7) The metal hydroxide materials overviewed in the previous sections possess specific macro and meso structures, and thereby, exhibit characteristic chemical/physical properties. The author and co-authors have reported the enhancement of dye adsorption 35) and protein adsorption 53) on hierarchically porous MgAl LDH. In the case of dye adsorption (Rhodamine B and Pyranine), larger macropores resulted in faster adsorption on LDH.…”
Section: Applications Of Metal Hydroxides With Controllable Nano/macrmentioning
confidence: 99%
“…7) The metal hydroxide materials overviewed in the previous sections possess specific macro and meso structures, and thereby, exhibit characteristic chemical/physical properties. The author and co-authors have reported the enhancement of dye adsorption 35) and protein adsorption 53) on hierarchically porous MgAl LDH. In the case of dye adsorption (Rhodamine B and Pyranine), larger macropores resulted in faster adsorption on LDH.…”
Section: Applications Of Metal Hydroxides With Controllable Nano/macrmentioning
confidence: 99%
“…In limiting the capillary forces which occur during drying, supercritical drying is well-known as an efficient process to produce highly porous aerogels [45]. LDH aerogels were produced using LDH wet physical gels by applying water exchange with a non-aqueous solvent and subsequent CO2 supercritical drying [46,47]. Even if monoliths are not systematically obtained, such treatment induces a net increase of the mesoporosity compared to standard ambient drying.…”
Section: Post-treatmentmentioning
confidence: 99%
“…The introduction of porosity, especially large mesopores and/or macropores, can increases the surface area which is accessible by large biomolecules with tens nm in size. High-density protein loading on porous LDH was reported for trypsine [47] and bovine serum albumin (BSA) [46,121], where enhancement of adsorption were reported as 20 times and 14 times compared to those for standard LDH, respectively (Table 6). There has been also various reports on loading and releasing an antibiotic [85], drug [128], enzyme [47], glucose biosensor development [122,134] and tissue-engineering scaffolds [49].…”
Section: Bio-applicationsmentioning
confidence: 99%
“…Similarly, CeO 2 catalyst or nanosized NiO could be synthesized through sacrificial template of albumin [41,42]. Deoxyribonucleic acid was utilized to prepare Co 9 S 8 nanoparticles with mesoporous internal structure [43], or to synthesize porous transition metal oxide [44]. It was also reported that porous alumina was obtained by collagen.…”
Section: Introductionmentioning
confidence: 99%